1159 Sleep Traits And Incident Delirium During A Decade Of Follow-up In 173, 000 Participants. (27th May 2020) - Gao, L; Li, P; Cui, L; Johnson-Akeju, O; Hu, K
Abstract: Introduction: Delirium is an acute decline in attention and cognition that is with associated long-term cognitive dysfunction in elderly patients. Accumulating evidence points to strong associations between sleep health and disorders of the brain. We tested whether baseline sleep duration, chronotype, daytime dozing, insomnia or sleep apnea predict incident delirium during hospitalization. Methods: We studied participants from the UK Biobank who have been followed for up to 10 years until 2017. We included 173, 221 participants (mean age 60±5; range 50-71 at baseline) who had at least one episode of hospitalization/surgery and were free from prior episodes of delirium. Delirium diagnosis, hospitalization and surgical events were derived using ICD-10 coding. Multivariate logistic regression models were performed to examine the associations of self-reported baseline sleep duration (<6hrs/6-9h/>9h), daytime dozing (often/rarely), insomnia (often/rarely) and presence of sleep apnea (ICD-10 and self-report) with incident delirium during follow-up. Models were adjusted for demographics, education, Townsend deprivation index, and major confounders (number of hospitalizations/surgical procedures, BMI, diabetes, major cardiovascular diseases and risk factors, major neurological diseases, major respiratory diseases, cancer, alcohol, depression/anxiety, sedatives/sleep aides, antipsychotics, steroids and opioids). Results: In total, 1, 023 (5.7 per 1, 000 subjects) developed delirium. A prior diagnosis of sleep apnea (n=1, 294) saw almost a two-fold increased odds (OR 1.96, 95% CI: 1.30-2.30 p =0.001) while those who often had daytime dozing were also at increased risk (OR 1.35, 95% CI: 1.02-1.80, p =0.025). Both these effects were independent of each other. No independent effects on incident delirium were observed from sleep duration, insomnia, or chronotype. Conclusion: Certain sleep disturbances, in particular sleep apnea and daytime dozing, are independently associated with an increased risk for developing delirium. Further work is warranted to examine underlying mechanisms and to test whether optimizing sleep health can reduce the risk of developing delirium. Support: This work was supported by NIH grants T32GM007592, RF1AG064312, and RF1AG059867.